SELEKSI KETAHANAN BIBIT KAKAO (Theobroma cacao L.) TERHADAP POLYETHYLENE GLYCOL - M.Taufiq Hidayat (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2015)
Increased cocoa production can be done with the improvement of plants adapted to marginal lands include dry land. One effort that can be done is to do a selection of some cocoa clones that have the potential tolerant of drought stress. Compound polyethylene Glycol (PEG) is a compound that can be used to simulate the conditions of dry land. This study aims to determine the effect of PEG treatment on the various clones of cocoa. Research carried out in a Random Design Group (RAK) is arranged in a factorial, repeated 3 times. The first factor is the planting material / clone. The second factor is the concentration of PEG, which consists of 5 levels, Observations were made on plant height, stem diameter, number of leaves, leaf area, plant dry weight, wet weight of plants, the main root length, number of branches of secondary roots, the number of stomata and electrical conductivity. The results showed that there was no interaction between planting materials / clones with PEG concentration of all observation parameters, types of planting materials / cacao clones ICS 60 is a clone that has an average growth of the best seeds.